Germline mutations in DNA repair genes predispose asbestos-exposed patients to malignant pleural mesothelioma. (1st October 2017) - Betti, Marta; Casalone, Elisabetta; Ferrante, Daniela; Aspesi, Anna; Morleo, Giulia; Biasi, Alessandra; Sculco, Marika; Mancuso, Giuseppe; Guarrera, Simonetta; Righi, Luisella; Grosso, Federica; Libener, Roberta; et al.
Abstract: Malignant pleural mesothelioma (MPM) is a rare, aggressive cancer caused by asbestos exposure. An inherited predisposition has been suggested to explain multiple cases in the same family and the observation that not all individuals highly exposed to asbestos develop the tumor. Germline mutations in BAP1 are responsible for a rare cancer predisposition syndrome that includes predisposition to mesothelioma. We hypothesized that other genes involved in hereditary cancer syndromes could be responsible for the inherited mesothelioma predisposition. We investigated the prevalence of germline variants in 94 cancer-predisposing genes in 93 MPM patients with a quantified asbestos exposure. Ten pathogenic truncating variants (PTVs) were identified in PALB2, BRCA1, FANCI, ATM, SLX4, BRCA2, FANCC, FANCF, PMS1 and XPC. All these genes are involved in DNA repair pathways, mostly in homologous recombination repair. Patients carrying PTVs represented 9.7% of the panel and showed lower asbestos exposure than did all the other patients (p = 0.0015). This suggests that they did not efficiently repair the DNA damage induced by asbestos and leading to carcinogenesis. This study shows that germline variants in several genes may increase MPM susceptibility in the presence of asbestos exposure and may be important for specific treatment. Highlights: We show that germline mutations in DNA repair genes may predispose to MPM. Mutation carriers showed lower asbestos exposure compared with the other patients. Abnormal DNA repair may favor MPM carcinogenesis due to asbestos exposure.